ANALISIS KELAYAKAN NASABAH DALAM PEMINJAMAN DI BPR OPHIR UJUNG GADING PASAMAN BARAT - Nurhayati Nurhayati; Yossi Eriawati; Feri Oki Nofendra (At Tasyri'i : Jurnal Program Studi Perbankan Syariah, 2023)
This study departs from the problems that occur in banking in terms of lending caused by several factors including, bank management in conducting inaccurate loan analysis, weak loan financing supervision, inaccurate financial analysis and weak competence of human resources. The purpose of this study is to determine how the feasibility analysis of customers in lending at BPR Ophir Ujung Gading West Pasaman. This study uses a qualitative approach. The type of research used in this research is field research or field studies. The data obtained from this study are primary data and secondary data obtained from the BPR Ophir Ujung Gading Pasaman Barat. And technical data analysis using field research or observation (field research), interviews and Documentation Studies.